2008
DOI: 10.1161/circresaha.107.169896
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of PTEN in Smooth Muscle Cells Results in Vascular Remodeling and Recruitment of Progenitor Cells Through Induction of Stromal Cell–Derived Factor-1α

Abstract: Abstract-We previously showed that changes in vascular smooth muscle cell (SMC) PTEN/Akt signaling following vascular injury are associated with increased SMC proliferation and neointima formation. In this report, we used a genetic model to deplete PTEN specifically in SMCs by crossing PTEN LoxP/LoxP mice to mice expressing Cre recombinase under the control of the SM22␣ promoter. PTEN was downregulated with increases in phosphorylated Akt in major vessels, hearts, and lungs of mutant mice. SMC PTEN depletion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 42 publications
4
93
0
Order By: Relevance
“…Rosiglitazone failed to significantly increase PTEN expression in normoxic mice, suggesting that rosiglitazone-mediated attenuation of hypoxia-induced reductions in PTEN expression may be more complicated than simple stimulation of the PTEN promoter. The potential importance of reduced PTEN in pulmonary hypertension is further supported by evidence that genetic interruption of PTEN in vascular smooth muscle caused development of pulmonary hypertension and vascular remodeling in mice exposed to normoxia (22). These reports, along with the current study, suggest that CH stimulates PDGF signaling not only through enhanced PDGFRb expression in the lung, but also by inhibiting the expression of the regulatory phosphatase, PTEN.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Rosiglitazone failed to significantly increase PTEN expression in normoxic mice, suggesting that rosiglitazone-mediated attenuation of hypoxia-induced reductions in PTEN expression may be more complicated than simple stimulation of the PTEN promoter. The potential importance of reduced PTEN in pulmonary hypertension is further supported by evidence that genetic interruption of PTEN in vascular smooth muscle caused development of pulmonary hypertension and vascular remodeling in mice exposed to normoxia (22). These reports, along with the current study, suggest that CH stimulates PDGF signaling not only through enhanced PDGFRb expression in the lung, but also by inhibiting the expression of the regulatory phosphatase, PTEN.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, PTEN is inhibited by ROS (18,19), and its expression can be stimulated by PPARg ligands (20,21). On the other hand, smooth muscle-targeted depletion of either PTEN (22) or PPARg (23) caused pulmonary hypertension in mice. Collectively, these findings prompted our examination of PPARg and its ability to regulate PDGF and PTEN signaling pathways in the lung during hypoxia.…”
mentioning
confidence: 99%
“…52,53 Suppression of PI3K reduces neointima formation, 54 whereas suppression of phosphatase and tensin homolog increases SMC hyperplasia. 55 In this study, we found that XBP1 splicing contributed to neointima formation via regulating SMC migration and proliferation. High levels of XBP1 expression and splicing could be detected immediately post vascular injury, whereas XBP1 deficiency in SMC significantly reduced neointima formation.…”
Section: Discussionmentioning
confidence: 58%
“…Deleris et al (11) found that PTEN is also expressed and active in VSMCs controlling the level of PIP3 and therefore potentially controlling VSMC proliferation. Another report (27) showed that absence of PTEN in VSMCs leads to vascular remodeling and increased progenitor cell recruitment. However, to date, the specific deletion of Pten in lung mesenchyme during development has not been reported.…”
Section: Mesodermal Pten Inactivation Disrupts Lung Vasculogenesismentioning
confidence: 99%